The effect of retinal defocus on simple eye-hand and eye-foot reaction time in traumatic brain injury (TBI). (December 2013) - Gould, Jennifer A.; Ciuffreda, Kenneth J.; Yadav, Naveen K.; Thiagarajan, Preethi; Arthur, Benjamin
Abstract Primary objective: The purpose of the experiment was to assess the effect of retinal defocus on simple eye-hand (E-H) and eye-foot (E-F) reaction time (RT) in traumatic brain injury (TBI). Design and methods: Sixteen subjects with traumatic brain injury (five males and 11 females; aged 22–34 years) participated in the experiment. These were compared with 16 visually-normal, age/gender-match subjects. Retinal defocus was introduced optically (plano, +1, +2, +3, +4, +10D and +2D × 90) in the spectacle plane with binocular viewing. E-H and E-F RT were assessed binocularly using the RT-2S Simple Reaction Time Tester (Advanced Therapy Products, Glen Allen, VA). The test target colour and angular subtense simulated a conventional red/green traffic signal at 120 feet. Results: There was no significant effect (p > 0.05) of retinal defocus on either E-H or E-F RT in each population. There was a significant effect (p < 0.05) of TBI on both E-H and E-F RT as compared with the normative data, with it being longer and more variable in TBI. Each RT condition was longest in those with moderate TBI. Conclusions: Both RTs were robust to retinal defocus, thus suggesting central nervous system insensitivity for this simple RT task. However, the increased RTs and related variability found in TBI, especially in moderate TBI, have potential safety implications (e.g. driving a car, ambulating).